Realization of Air Protection Repair Program in Warsaw agglomeration - Jawor, Alicja; Skowroński, Antoni (Studia Ecologiae et Bioethicae, 2010)
The aim of the present article is to approach the problems connected with air pollution and also with different types of scientific, legal and administrative activities in the field of atmosphere protection. The research has been carried out on the territory of the Warsaw agglomeration. In connection with this fact, all means of administration are referred to as the present political and economical conditions of the Warsaw agglomeration. Air Protection Repair Program (NPOP), making up the content of the present work, introduces the resolutions in the field of management of the quality of the air based on the norms used on the territory of the European Union and shows governmental activities directed to the attainment of a common standard of the development of the capital at the arena of other European agglomerations.